A forward-modelling method to infer the dark matter particle mass from strong gravitational lenses. Issue 2 (28th January 2022) - He, Qiuhan; Robertson, Andrew; Nightingale, James; Cole, Shaun; Frenk, Carlos S; Massey, Richard; Amvrosiadis, Aristeidis; Li, Ran; Cao, Xiaoyue; Etherington, Amy
ABSTRACT: A fundamental prediction of the cold dark matter (CDM) model of structure formation is the existence of a vast population of dark matter haloes extending to subsolar masses. By contrast, other dark matter models, such as a warm thermal relic (WDM), predict a cutoff in the mass function at a mass which, for popular models, lies approximately between 10 7 and 10^10 M_ . We use mock observations to demonstrate the viability of a forward modelling approach to extract information about low-mass dark haloes lying along the line of sight to galaxy–galaxy strong lenses. This can be used to constrain the mass of a thermal relic dark matter particle, m DM . With 50 strong lenses at Hubble Space Telescope resolution and a maximum pixel signal-to-noise ratio of ∼50, the expected median 2σ constraint for a CDM-like model (with a halo mass cutoff at 10^7 M_ ) is m_DM 4.10 keV (50 per cent chance of constraining m DM to be better than 4.10 keV). If, however, the dark matter is a warm particle of m_DM=2.2 keV, our 'approximate Bayesian computation' method would result in a median estimate of m DM between 1.43 and 3.21 keV. Our method can be extended to the large samples of strong lenses that will be observed by future telescopes and could potentially rule out the standard CDM model of cosmogony. To aid future survey design, we quantify how these constraints will depend on data quality (spatial resolution and integration time) as well as on the lensing geometry (source and lens redshifts).